KERAGAMAN DAN HUBUNGAN FENETIK SPESIES IKAN ANGGOTA KELAS OSTEICHTHYES DI PERAIRAN LAMONGAN, PASURUAN DAN SITUBONDO, JAWA TIMUR - , Dwi Oktafitria ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Fishery products are abundant in the nothern coast of East Java, especially Lamongan, Pasuruan, and Situbondo not necessarily have a high diversity of species, as well as possible differences in the condition of water have different species composition. This study was conducted to determine the diversity, characters and phenetic relationship of fish spesies a member of the class Osteichthyes in Lamongan waters, Pasuruan and Situbondo. The study was conducted in November-Desember 2012. Methods is using longline fishing. Morphological character data hereafter devised scooring by numerical methods. Data were analyzed using the software program approach MVSP 3.1A with UPGMA ( Unweighted Pair Group Method Arithmetic) methods to get a dendogram. The result showed that found 5 order, 22 families, 28 genera and 41 species. All the data, whic h is the dominant order is Perciformes and the dominant species is Nemipterus isacanthus (Kurisi). The main morphological character that distinguish of fish species a member of the class Osteichthyes in marine waters Lamongan, Pasuruan and Situbondo such as presence or absence of scale, presence or absence of fins (pelvic fin, adipose fin), dorsal fin shape, the number of finger and rays pelvic fin and colour pattern (stripes, bar, blotch, spot). Dendogram of fish species a member of the class Osteichthyes shows there are 3 clusters of fish with 1 out group. The first cluster is a member Aulopiformes, the second cluster is a member Clupeiformes, the third cluster is a member of Perciformes and out group is a member Tetraodontiformes. This study concluded that there are 41 species have variety morphological characters and based on similarity can be grouped into three clusters and 1 out group.